EFEKTIVITAS PEMBERIAN JAHE DAN KUNYIT ASAM TERHADAP PENURUNAN DISMENOREA PADA REMAJA PUTRI DI ASRAMA ABIM KECAMATAN MOJOROTO KOTA KEDIRI TAHUN 2016 - Anggraeni, Ria mei; Prasetyanti, Dhita kris; aminah, Siti (Jurnal Mahasiswa Kesehatan, 2019)
Dysmenorrhea is a pain during menstruation characterized by cramps in the lower abdomen. Based on the preliminary survey through interview on 10 female teenagers in Asrama Abim at October 28th , 2016, the result showed that 7 (70%) teenagers had dysmenorrhea and 3(30%) did not have dysmenorrhea. The objective of this research is to know the effectiveness of ginger and tamarind curcuma in reducing dysmenorrhea in Asrama Abim Mojoroto sub district Kediri City in 2016. The research design used Quasy Experiment. The population were 32 female teenagers in Asrama Abim taken through accedental sampling. The sampels divided into two group which group of 16 teenagers given ginger and two group of 16 given tamarind curcuma. The research instrument used Numerical Rating Scale (NRS) and obervation sheet. Research result analyzed by Wlcoxon Signed Rank and Mann-Whitney Signed Rank Tests. Based on the result (p=0,000<0,05) showed that there is effectiveness before and after given ginger on dysmenorrhea, and there is effectiveness before and after given tamarind curcuma on dysmenorrhea. The result of analysis showed that ginger is more effective in reducing there is dysmenorrhea of female teenagers in Asrama Abim Mojoroto Sub district Kediri City in 2016. It is expected for respondents to use ginger to relieve the pain of dysmenorrhea, which a non-pharmacologic is easy to use and effective in reducing the physical complaints of menstruation.Â Keywords: Ginger, Tamarind Curcuma, Dysmenorrhea, and teenage girl.